Potential auxiliary diagnostic role of pentraxin 3 in plasma and bronchoalveolar lavage fluid for pulmonary tuberculosis - Xiufeng Huang; Hongxing Li; Lu Liu; Yu Zhang (Journal of Cardiothoracic Surgery)
Abstract Objective This study aimed to assess the auxiliary diagnostic efficacy of Pentraxin 3 (PTX3) as a biomarker for pulmonary tuberculosis (TB) by analyzing its levels in plasma and bronchoalveolar lavage fluid (BALF) in TB patients. Given the limitations of current TB diagnostic methods, the investigation also sought to evaluate the possible auxiliary help of PTX3 in distinguishing TB from other pulmonary conditions. Methods The bioinformatic analysis utilized the Gene Expression Omnibus (GEO) dataset (GSE34608), including peripheral blood samples from individuals with TB, sarcoidosis, and healthy controls. Clinical specimens were obtained from hospitalized patients between January 2020 and March 2022, comprising 126 peripheral blood samples and 68 BALF samples. PTX3 levels were measured via enzyme-linked immunosorbent assays (ELISA), with subsequent statistical analyses conducted to assess the auxiliary diagnostic efficacy of PTX3 through ROC curve analysis. Results The analysis of the GEO dataset revealed a notable increase in PTX3 levels in the peripheral blood of TB patients compared to controls, with an area under the curve (AUC) of 0.889. However, no significant differences in plasma PTX3 levels were observed among TB, community-acquired pneumonia (CAP), and lung cancer patients in clinical samples (AUC: 0.472). Conversely, PTX3 levels in BALF were significantly elevated in TB patients compared to individuals with CAP and lung cancer (P < 0.001), with an AUC of 0.806, along with a sensitivity of 0.800 and specificity of 0.810, suggesting its potential auxiliary diagnostic utility. Conclusion Plasma PTX3 levels have limited diagnostic utility in distinguishing tuberculosis from other pulmonary conditions, whereas BALF PTX3 levels exhibit more possible auxiliary diagnosis ability as an auxiliary diagnostic indicator, offering a localized assessment of lung inflammation. BALF PTX3 could be a helpful adjunct in diagnosing TB, particularly in cases where conventional sputum-based tests are inconclusive. Further research is needed to validate these findings.